English Department Students’ Problems in Writing Research Proposal - Roza Susanti; Dwi Settya Mahaputri (Pustaka Galeri Mandiri, 2022)
Proposal is a scientific writing done by the fourth year students as one of the fulfilments to get undergraduate degree. Students had difficulties in writing the proposal such as developing the introduction of the proposal, discussing the related theories and findings, methodology and also in terms of language components: grammar, vocabulary, and organization of ideas in paragraphs. The purpose of this research was to know what are the fourth year students’ problems in writing proposal. This research was a descriptive research. The participants was all the fourth year students of English department of STKIP Abdi Pendidikan Payakumbuh. The participants was chosen by using purposive sampling. The instrument used was questionnaire. Based on the result, it was shown that the most difficult part of writing proposal is introduction, writing the background of the problem and also in formulating the purpose of the research. Next, the students got problem in literature review, writing the related findings and also the coverage of the related theories. After that, the students got problem in methodology, especially in writing the procedures of doing the research. Finally, the students got problem in writing the bibliography especially in writing references for articles or journals without the writers’ names.